Antiviral Effect of Different Essential Oils on Avian Coronavirus - Okino, Cintia Hiromi; Melito, Glaucia Roberta; Astolfo, Maria Eduarda de Almeida; Martins, Maria Eduarda Da Mata [UNESP]; Bogusz Jr, Stanislau; Ferreira, Marcos David (Amer Assoc Avian Pathologists, 2024)
Plant essential oils (EOs) possess established antimicrobial properties; however, research on their antiviral activity, particularly against avian coronaviruses, remains limited. EOs offer a promising plant-based alternative for viral control, especially in scenarios where conventional chemical use is restricted. This study aimed to evaluate the antiviral effects of six different essential oils derived from Syzygium aromaticum,Origanum , Origanum vulgare, , Cymbopogon martinii, , Cymbopogon citratus, , Mentha piperita,, Mentha spi- cata against avian coronavirus (AvCov) at 0.1% , 1% dilutions. The antiviral effects of the EOs were assessed via virus isolation from embryonated chicken eggs, and the ability of the EOs to inhibit AvCoV replication was evaluated. The EOs from Syzygium aro- maticum,Origanum , Origanum vulgare, , Cymbopogon martinii, , Cymbopogon citratus completely inhibited AvCov replication at a 1% dilution. Conversely, absent to partial inhibitory effect was observed at the 0.1% dilution for all tested EOs, with O. vulgare derived EO exhibiting the greatest inhibitory effect (over 70%). Notably, EOs from Mentha piperita and Mentha spicata were unable to com- pletely inhibit AvCov at either concentration. Our fi ndings highlight the potent antiviral activity of the EOs from Syzygium aromati- cum,Origanum , Origanum vulgare, , Cymbopogon martinii, , and Cymbopogon citratus against AvCov at a 1% dilution. The complete inhibition observed for these EOs suggests their potential for AvCov control. However, further research is necessary to elucidate the mechanisms of action, optimize formulations, and evaluate the efficacy fi cacy against other coronaviruses, including those relevant to human health.
Keywords: antiviral; RTqPCR; chicken; viral load; infectious bronchitis virus